Unveiling The Corporeal: The Female Body, Subjectivity and Politics of Visibility in Maryam Touzani’s Film Adam - Namrok, Meriem (Integrated Journal for Research in Arts and Humanities, 2024)
Throughout the history of cinema, the female body has often been a scopic site of pleasure and subjugation. Female filmmakers have long sought to refute the sexist scrutiny of women onscreen and work for healthier cinematic representations of the female body. This article aims to cast light on the different textual and visual tactics and aesthetics employed by the transnational Moroccan filmmaker Mariam Touzani in her film Adam (2020) to de-romanticize women and deconstruct the conventional cinematic framework where the female body is restrained to adhere to the patriarchal ideologies. The female protagonists Samia and Abla reflect the determination of the filmmaker Mariam Touzani to provide an understanding of the female body as an organism full of life, emotions, and agency, rather than an erotic, static icon. In analysing the film, the article embraces a feminist discourse to highlight the multifaceted dimensions of womanhood and contemplate the complexities surrounding the female body. Adam is a feminist firebrand against the alienating conditions of women and the objectification of the female body.